Synergistic effect of standardized extract of Asparagus officinalis stem and heat shock on progesterone synthesis with lipid droplets and mitochondrial function in bovine granulosa cells. Issue 225 (January 2023) - Ho, Khoi Thieu; Balboula, Ahmed Zaky; Homma, Kohei; Takanari, Jun; Bai, Hanako; Kawahara, Manabu; Thi Kim Nguyen, Khang; Takahashi, Masashi
Abstract: Progesterone (P4) is a well-known steroid hormone that plays a key role in oocyte growth and the maintenance of pregnancy in mammals, including cattle. Heat stress (HS) has an adverse effect on P4 synthesis through an imbalance in the cellular redox status. We have recently revealed that a standardized extract of Asparagus officinalis stem (EAS) increases P4 through non-HS induction of heat shock protein 70 (HSP70) and a synergistic increase of HSP70 by enhancing the intracellular redox balance, which was adversely affected by HS in bovine granulosa cells (GCs). Bovine GCs collected from bovine ovarian follicles were cultured at 38.5 °C and 41 °C for 12 h with or without 5 mg/mL EAS. After treatment, cells and culture suppernatant were collected for the analysis. Enzyme-linked immunosorbent assay (ELISA) was performed to detect in P4 levels. Quantitative reverse-transcription polymerase chain reaction (RT-qPCR) was used to detect expression of steroidogenesis related genes. Fluorescence staining was used to detect mitochondrial activity and lipid droplet. P4 level was increased by EAS treatment in association with increase in steroidogenic acute regulatory protein (STAR), 3β-hydroxysteroid dehydrogenase (3β-HSD), mitochondrial membrane activity and lipid droplet both under non-HS and HS conditions. Notably, synergistic effect of EAS with HS co-treatment was observed to show a greater increase in P4 synthesis when comparison with EAS treatment under non-HS condition. Furthermore, inhibition of HSP70 significantly reduced EAS-induced P4 synthesis, mitochondrial activity and synthesis of lipid droplets. These results suggest that P4 synthesis by EAS is mediated by the steroidogenesis pathway via HSP70-regulated activation of STAR and 3β-HSD, together with improved mitochondrial activity and lipid metabolism in bovine GCs. Moreover, effect of EAS has a synergistic effect of with HSP70-regulated steroidogenesis pathway. Graphical Abstract: ga1 Highlights: EAS increases progesterone synthesis by increasing of steroidogenesis-related genes. EAS increases lipid synthesis and mitochondrial activity. Synnergistic effect of EAS and heat shock on progesterone synthesis. HSP70 inhibition decreases EAS-stimulated progesterone synthesis pathway.